PERANCANGAN ALAT BANTU KERJA BERDASARKAN ANALISIS POSTUR KARYAWAN DI PT CITRA TUBINDO TBK KOTA BATAM - Josef; Sri Zetli (Computer Science and Industrial Engineering, 2024)
The current rapid technological advancement allows companies to increase production speed through the use of machinery. However, this often leads to monotonous and physically demanding work, especially in Manual Material Handling (MMH) activities. Inappropriate MMH activities can result in Musculoskeletal Disorders (MSDs), involving disruptions to muscles and joints. To address this issue, the design of ergonomic work aids is necessary.The NIDA method (Need, Idea, Decision, Action) is employed to design work aids by considering needs, innovative ideas, design decisions, and implementation actions. The REBA method (Rapid Entire Body Assessment) to assess the working position or posture of an operator’s neck, back, arms, wrists, and legs . Research results indicate that the use of specialized aids in activities such as measurement can reduce MSDs complaints, where the score on employee body posture analysis is obtained on averange 3 and the NBM questionnaire date shows an averange score of 30, whwere this score included in the low risk category. And before the work facility design was carried out, the score was for REBA 6 and with NBM questionnaire data 41, the category indicates medium risk. Previous research has also utilized the NIDA method in designing work aids with positive outcomes. In conclusion, the use of the NIDA method in designing ergonomic work aids can alleviate MSDs complaints and enhance productivity at PT Citra Tubindo TBK and similar industries.